Historical and Philosophical Overview of the Law of Ancient Cyprus up to Roman Times - Charalampos Stamelos (Journal on European History of Law)
In the present study we examine historical and philosophical aspects of the law of ancient Cyprus from the foundation of the Kingdoms to their abolition and the transformation of Cyprus into a Roman province. From this study, useful, timeless and timely conclusions emerge for the broader perception and understanding of the concepts of ethics, justice, good law-making and law in general. The analysis includes public law, private law and criminal law of Ancient Cypriot Kingdoms. Moreover, there is an analysis of philosophical aspects of Ancient Cyprus which was similar to Ancient Greek philosophy influenced the respective laws.